The Cambridge Introduction to Mark Twain - Messent, Peter, 1946- (Cambridge, UK ; New York : Cambridge University Press, 2007)
"This introduction provides a biography of the author and situates his works in the historical and cultural context of his times. Peter Messent gives readings of the best-known writings including Tom Sawyer and Huckleberry Finn. He pays particular attention to the way Twain's humour works and how it underpins his prose style. The final chapter provides up-to-date analysis of the recent critical reception of Twain's writing, and summarises the contentious and important debates about his literary and cultural position."--BOOK JACKET.
Mark Twain's life -- The early life -- Riverboating, the Civil War, the west -- Early success, marriage, the Hartford years -- Expatriation, financial loss, family tragedy -- The final years -- Contexts -- Samuel Langhorne Clemens and 'Mark Twain' -- Works -- Twain's humour -- Travel and travel writing : Innocents abroad, A tramp abroad, Roughing it, Life on the Mississippi -- Tom Sawyer and Huckleberry Finn -- A Connecticut yankee and Pudd'nhead Wilson -- Critical reception and the late works -- Guide to further reading.
Includes bibliographical references (p. 127-131) and index.
Keywords: Twain, Mark, -- 1835-1910 -- Handbooks, manuals, etc; Authors, American -- 19th century -- Biography -- Handbooks, manuals, etc; Twain, Mark, -- (1835-1910); Twain, Mark